Planificación Estratégica de la Cooperativa de Ahorro y Crédito 22 de Junio de la Parroquia Orianga Cantón Paltas, Periodo 2017 – 2022 - Machuca Córdova, Mariuxi Maricela (2017)
The present work is a prescriptive research. The starting point was the determination of the objectives of the study, being the following; To carry out strategic planning as a general objective and within the specific objectives to carry out an economic economic diagnosis and to determine strategies, activities and budget for this cooperative, the same ones that marked the route of the procedures, actions and analysis of the present work. The core of the work consisted in carrying out the external analysis from which the necessary information was obtained to elaborate the matrix EFE (matrix of evaluation of external factors), as well as the realization of the matrix of the competitive profile MPC. The analysis of the internal factors was carried out, for which the surveys were applied to both the internal and external actors and the financial diagnosis with the application of indicators PERLAS; the information obtained served as a basis for the elaboration of the EFI matrix (internal factor evaluation matrix). With the information obtained through the analysis of both external and internal factors, the SWOT matrix was elaborated and, from the technical conjugation of the FO - FA - DO - DA crosses, The strategies for that entity; In order to determine the position of the strategy profile for the cooperative, the strategic position matrix and evaluation of PEYEA actions were applied and the MPEC quantitative strategic planning matrix was completed, through which it was possible to classify, identify and select in order the strategies for the entity. The structure of the strategic objectives is nuanced by the determination of Strategy, Activities, Policy, Lines of Action, Resources, Time and Responsible for its fulfillment, Expected Results, Financing, Development and Budget. In the complementary part of the thesis work, the conclusions are made with the respective recommendations, which generate an important contribution in the research carried out. Executed the work is concluded that the lack of a strategic address, prevents the "Cooperative Savings and Credit June 22." Develop economically in the local market; So it is recommended to implement this proposed strategic plan, as it is directed to the creation of strategies according to the needs and expectations of the institution and its partners, allowing managers to make timely decisions, thus providing an address and bases Solid to consolidate its growth in the financial market, efficiently taking advantage of its resources to reach the proposed objectives, with an adequate and efficient administrative management.